Experimental Tests of the Function and Flexibility of Song Consistency in a Wild Bird. (3rd February 2016) - Taff, Conor C.; Freeman‐Gallant, Corey R.
Abstract: Measures of bird song that capture aspects of motor performance, such as consistency, have become a major focus in understanding sexual selection on song. Despite accumulating evidence that consistency is related to reproductive success in many species, the relative importance of male–male interactions and female–male interactions is still unclear. We studied the function and flexibility of song consistency and song rate in common yellowthroat warblers ( Geothlypis trichas ). A previous study of this population found that song consistency—measured as the amount of variability within a bout of songs—was positively correlated with the likelihood of siring extrapair young. In this study, we conducted two experiments aimed at testing (1) the role of song consistency and rate in mediating male–male and male–female interactions and (2) whether song effort is flexibly adjusted to changes in social context. In the first experiment, we simulated a male territorial intrusion with song playbacks that varied in consistency and rate; focal males responded aggressively to playbacks, but their response did not differ with playback consistency or rate. In the second experiment, we presented focal males with a taxidermic female mount and female vocalizations; focal males approached the speaker, but continued to sing and did not perform the aggressive rattle vocalization observed during male encounters. Immediately after the simulated female encounter, focal males increased in song consistency. Taken together, our results are most consistent with the hypothesis that song consistency in common yellowthroats is primarily a female‐directed signal that is actively adjusted in response to rapidly changing social conditions.